Boriding bearing steel and preparation method thereof
By forming a boron seepage layer of specific thickness on 20CrNiMo low-carbon bearing steel and combining with appropriate tempering treatment, the problem of boron seepage process reducing the toughness of bearing steel is solved, and the wear resistance and toughness of bearing steel is significantly improved, and it is suitable for bearings of tooth drill bits.
Patent Information
- Application Number
- CN202411712358.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-27
AI Technical Summary
The existing boron penetration process will reduce the toughness of low-carbon bearing steel to a certain extent and affect its service life.
By forming a boron bleed layer of specific thickness on the substrate surface of the 20CrNiMo low-carbon bearing steel, a boron bleed agent composed of Na2B4O7, Al, and KCl is used for salt bath boron bleed, and combined with water quenching and boiling and boiling water, the thickness and component ratio of the boron bleed layer are controlled to improve the toughness and wear resistance of the bearing steel.
It significantly improves the surface hardness, wear resistance, strength and toughness of bearing steel, and extends the service life of the gear drill bit bearing.
Smart Images

Figure CN119530675A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of bearing steel, and more specifically, to a boronized bearing steel and a preparation method thereof. Background Art
[0002] The roller drill bit is the main rock-breaking tool in oil and gas development projects. It breaks the formation rock by impact, crushing and shearing. Among them, the bearing is the main component of the roller drill bit. The roller drill bit will be unable to continue working due to the failure of the bearing during operation. The life of the bearing directly determines the life of the roller drill bit.
[0003] In addition to failure due to brittle fracture, there are two other important failure phenomena during the use of bearings, namely wear failure and corrosion failure. Wear failure and corrosion failure are mostly caused by damage to the bearing surface or near the surface. This is because the bearing surface is more severe than the internal working environment, which often leads to early damage. Therefore, in order to increase the service life of bearings, further surface strengthening measures must be taken on the basis of the overall high strength and toughness of bearing steel. Among them, the surface chemical heat treatment process is to form a compound layer (infiltration layer) with special physical and chemical properties on the surface of the material, and through metallurgical bonding, the bonding strength between the infiltration layer and the matrix is higher, giving the material surface excellent properties such as high wear resistance and high corrosion resistance. It is often used in bearing material processing.
[0004] In order to improve the wear resistance of bearing steel, boronizing is one of the effective surface layer treatment methods. Compared with general chemical heat treatment methods, the boronized layer obtained by the boronizing process has the characteristics of high hardness and good wear resistance. However, although the boronized layer has the above-mentioned outstanding advantages, it has high brittleness. Especially for some low-carbon alloy steels (20CrNiMo, etc.), after quenching and low-temperature tempering after boronizing, the toughness will be reduced to a certain extent. Summary of the invention
[0005] In order to solve the problem that the existing boronizing process will reduce the toughness of low-carbon bearing steel to a certain extent, the present application provides a boronized bearing steel and a preparation method thereof, taking 20CrNiMo series low-carbon bearing steel as the research object, and forming a boronizing layer of a certain thickness on the surface of the matrix through specific matrix components and boronizing agents, which significantly improves the surface hardness, wear resistance, strength and toughness of the bearing steel.
[0006] In the first aspect, the present application provides a boronized bearing steel, comprising a substrate and a boronized layer; the substrate is 20CrNiMo steel, comprising the following components in weight percentage: C 0.18-0.22wt%, Si0.25-0.32wt%, Mn 0.75-0.83wt%, Cr 0.48-0.55wt%, Ni 0.50-0.70wt%, Mo 0.40-0.50wt%, V 0.18-0.21wt%, and the remainder is Fe and unavoidable impurities; the boronized layer is obtained by salt bath boronizing, and the boronizing agent of the salt bath boronizing is mainly composed of Na2B4O7, Al and KCl, and the weight ratio of Na2B4O7, Al and KCl is 1:0.06-0.10:0.5-0.6, and the thickness of the boronized layer is 20-80μm.
[0007] This application uses 20CrNiMo steel as the matrix. Controlling the carbon content is the key to improving the hardenability and hardenability of wear-resistant cast steel. If the carbon content is too low, a pearlite structure with low hardness and poor wear resistance will easily appear during quenching, and even if boronized, the corresponding bearing steel will hardly have high wear resistance; if the carbon content is too high, a large amount of high-carbon martensite with high brittleness will appear during quenching, thereby reducing the strength and toughness of the bearing steel, and its boronized layer will also easily crack or even peel off during use.
[0008] Although silicon dissolves into bearing steel, it can strengthen the matrix, but it will also make the matrix brittle to a certain extent, so its content in bearing steel needs to be strictly controlled; manganese can significantly improve the hardenability of bearing steel, but excessive manganese will lead to an increase in residual austenite, which will affect the wear resistance of bearing steel; chromium can improve the hardenability and tempering stability of bearing steel, but if the chromium content is too high, it will combine with carbon to form chromium carbide, which will further reduce the carbon content in the matrix. Therefore, the amount of carbon, silicon, manganese, and chromium in the matrix of this application needs to be strictly controlled within the set range to obtain a matrix with both excellent wear resistance and toughness.
[0009] The addition of nickel can refine the grains, distort the lattice of the bearing steel and hinder the dislocation movement, reduce the brittle transition temperature of the bearing steel, and thus improve the strength and toughness of the bearing steel, but too high a nickel content can easily reduce the high temperature resistance of the bearing steel; the present application appropriately increases the molybdenum content, which can not only effectively promote the uniform hardening of the bearing steel during the quenching process, but also supplement the high temperature resistance of the high content of nickel, but a higher molybdenum content will also increase the brittleness of the bearing steel; for this reason, a certain amount of vanadium is also added to the matrix of the present application, and vanadium can further refine the grains, and then cooperate with nickel to improve the toughness of the bearing steel, and combined with the high temperature stability characteristics of vanadium, it can effectively improve the high temperature strength of the bearing. Therefore, the present application ensures that the bearing steel has good high temperature resistance while having high toughness by limiting the content of nickel, molybdenum and vanadium, laying a good foundation for high temperature heat treatment during the salt bath boronizing process.
[0010] In addition, the present application adopts a salt bath boronizing process for boronizing, which can improve the utilization rate of the boronizing agent relative to solid boronizing, is safer than gas boronizing, and is more conducive to practical industrial applications. The boronizing agent uses sodium tetraborate as a boron source, which can react with metal aluminum to form a composite ceramic film of aluminum oxide-aluminum boride in a plasma chemical reaction, thereby improving the wear resistance and corrosion resistance of the boronized layer. The sodium tetraborate can also react with potassium chloride in a molten state to form sodium chloride and potassium tetraborate, which can be used as a flame retardant, rust inhibitor and adhesive on the one hand, which can not only increase the corrosion resistance and structural strength of the carburized layer itself, but also further increase the bonding stability of the carburized layer and the substrate; on the other hand, potassium tetraborate can also further react with metal aluminum to form a composite ceramic film of aluminum oxide-aluminum boride, and the composite ceramic film generated by it will have higher flexural strength and fracture toughness due to the bonding of potassium tetraborate.
[0011] However, in order to ensure the strength of the matrix in this application, metal aluminum and potassium chloride need to be added in appropriate amounts in the boriding agent. If the content of metal aluminum and potassium chloride is insufficient, it is difficult to form a uniform, intact and firmly bonded composite ceramic film layer; if the content of metal aluminum and potassium chloride is too much, the excess components will further penetrate into the matrix and affect the performance of the matrix. Therefore, this application strictly controls the weight ratio of each component in the boriding agent to enable the boriding agent to play an effective role.
[0012] On this basis, the thickness of the boriding layer will also affect the wear resistance and toughness of the low-carbon bearing steel to a certain extent. If the thickness of the boriding layer is thin, the boriding agent has not yet effectively played a role, and the bonding strength between the obtained boriding layer and the matrix is poor, and it is difficult to maintain a high wear resistance; if the thickness of the boriding layer is thick, it will affect the subsequent quenching of the bearing steel, and the toughness of the obtained borided bearing steel will decrease accordingly. Therefore, the present application combines the above-mentioned specific matrix components and the boriding agent, and then cooperates with the set thickness of the boriding layer, so that the obtained borided bearing steel has excellent wear resistance and toughness, and can be well used in the bearings of roller drill bits.
[0013] Preferably, the boronizing agent also includes NH4Cl.
[0014] Preferably, the weight ratio of Na2B4O7 to NH4Cl is 1:0.3-0.5.
[0015] By adopting the above technical scheme, ammonium chloride can, on the one hand, be used as a catalyst to promote the boronizing agent to effectively penetrate into the matrix for surface chemical heat treatment, thereby improving the bonding strength between the boronizing layer and the matrix; on the other hand, it can react with sodium tetraborate to generate boron nitride, and boron nitride reacts with aluminum in a molten state to generate aluminum nitride, which has good heat shock resistance, and its compounding in the boronizing layer can effectively improve the strength and toughness of the boronizing layer. In addition, since ammonium chloride decomposes to produce ammonia and hydrochloric acid in a heated state, the metal aluminum in the present application can adsorb the hydrochloric acid to generate aluminum chloride, effectively reducing the generation of hydrogen chloride gas by ammonium chloride during the boronizing process, thereby reducing the harm to personnel and the environment.
[0016] In actual operation, if the amount of ammonium chloride used is insufficient, it is difficult for it to effectively play the role of promoting penetration and reinforcing. If the amount of ammonium chloride used is too much, it is difficult for metallic aluminum to effectively absorb the hydrogen chloride produced by its decomposition. For this reason, this application needs to strictly control the amount of ammonium chloride added. When ammonium chloride is added according to the above weight ratio, the ammonium chloride can effectively act on the boriding reaction and reduce the escape of hydrogen chloride gas, which can not only improve the bonding strength between the boriding layer and the substrate, but also further improve the wear resistance, strength and toughness of the boriding layer.
[0017] In a second aspect, the present application provides a method for preparing a boronized bearing steel, comprising the following steps:
[0018] Preparing a 20CrNiMo steel billet: Preparing a 20CrNiMo steel billet according to the component ratio of the matrix;
[0019] Heat treatment: the boronizing agent is preheated and dehydrated, and then crushed to form a mixed powder. The 20CrNiMo steel billet is put into a salt bath furnace, a portion of the mixed powder is added first, and the temperature is raised to the austenitizing temperature. During the heating process, the remaining mixed powder is added in batches and stirred evenly. After the mixed powder is melted and no longer expands, the stirring is stopped, and the furnace cover is covered for insulation. After the insulation is completed, it is directly placed in water and quenched to room temperature to obtain a boronized bearing rough material;
[0020] Tempering: The boronized bearing rough material is first placed in boiling water for boiling and washing, then cleaned with alcohol, and then dried and stored in a vacuum to obtain the boronized bearing steel.
[0021] By adopting the above technical solution, the present application adds the boronizing agent in batches, which helps the boronizing agent to gradually react with the matrix and improve the reaction efficiency of the two. On this basis, the present application adopts the water quenching method to form lath martensite and flaky martensite in the matrix structure, and then uses boiling water for low-temperature tempering. The temperature of the boiling water is relatively constant, which helps to reduce the impact of the environment on the mechanical properties of the bearing steel. The matrix obtained in this way can better combine with the carburized layer and has higher toughness and strength.
[0022] Preferably, in the heat treatment step, the austenitizing temperature is 980-1030° C. and the holding time is 3-5 h.
[0023] With the above technical solution, the boronizing treatment is achieved by active atom diffusion, and the treatment temperature and time will affect the diffusion distance and concentration distribution of active atoms in the metal matrix. Due to the limited diffusion distance of active atoms, the affected area is mainly the transition zone between the boronized layer and the matrix and the core. The boron concentration in the transition zone is higher than that in the matrix core, and boron has a greater effect on the martensitic phase transformation. In addition, the expansion coefficient of borides (FeB and Fe2B) is large, and the matrix structure is squeezed during the formation process. The transition zone will have a certain degree of strain, which will affect the phase transformation and growth orientation of the transition zone. The phase transformation products and mechanical properties of the transition zone are important parameters that determine the bonding strength between the boronized layer and the matrix.
[0024] In this regard, the present applicant has found through research and experiments that when the heat treatment temperature is maintained at 980-1030°C for 3-5h, the corresponding boronized layer and the matrix are more tightly bonded, thereby obtaining boronized bearing steel with higher toughness and strength, so it is preferred.
[0025] Preferably, in the heat treatment step, the temperature is increased at a rate of 5-10°C / min.
[0026] When using the above technical solution, if the heating rate is too fast, too much austenite will remain and reduce the wear resistance of the matrix. If the heating rate is too slow, martensite with greater brittleness will be generated. Therefore, it is appropriate to control the heating rate to 5-10°C / min in this application.
[0027] Preferably, in the heat treatment step, the remaining mixed powder is added in two times, the first time when the system is heated to 650-700°C, and the second time when the system is heated to 800-850°C.
[0028] By adopting the above technical scheme, when the system is heated to 650-700°C, the sodium tetraborate and aluminum in the boriding agent are first melted into liquid. At this time, the remaining mixed powder is added for the first time, which helps the sodium tetraborate and the metal aluminum to react first to form a composite ceramic film layer. Subsequently, when the temperature is raised to 800-850°C, the remaining mixed powder is added for the second time. At this time, the potassium chloride melts and reacts with the sodium tetraborate, and the generated potassium tetraborate further reacts with the molten metal aluminum. The borided layer obtained has good wear resistance and toughness.
[0029] Preferably, in the tempering step, the boiling and washing time is 0.8-1.5h.
[0030] By adopting the above technical scheme, more salts will be attached to the surface of the borided bearing rough material obtained by heat treatment. The salts can be effectively cleaned by boiling and washing. However, if the boiling and washing time is too long, the borided layer on the surface will be damaged. In this application, 0.8-1.5h is appropriate.
[0031] In a third aspect, the present application provides a method for preparing a boronized bearing steel, comprising the following steps:
[0032] Preparing a 20CrNiMo steel billet: Preparing a 20CrNiMo steel billet according to the component ratio of the matrix;
[0033] Heat treatment: preheat and dehydrate Na2B4O7, Al, and KCl and grind them to form a mixed powder. Simultaneously, preheat and dehydrate NH4Cl and grind them to form NH4Cl powder. Put the 20CrNiMo steel billet into a salt bath furnace, add a portion of the mixed powder first, heat it to the austenitizing temperature, add the remaining mixed powder in batches during the heating process and stir evenly, add NH4Cl powder after the mixed powder is melted and continuously introduce ammonia, stop stirring after the system stops expanding, cover the furnace for insulation, and directly put it in water for quenching to room temperature after the insulation is completed to obtain a boronized bearing coarse material;
[0034] Tempering: The boronized bearing rough material is first placed in boiling water for boiling and washing, then cleaned with alcohol, and then dried and stored in a vacuum to obtain the boronized bearing steel.
[0035] By adopting the above technical scheme, the present application adds ammonium chloride after the boriding agent is completely melted. At this time, the sodium tetraborate, metallic aluminum and potassium chloride in the boriding agent have already preliminarily completed the reaction, thereby avoiding the competitive reaction of ammonium chloride with sodium tetraborate and metallic aluminum in the early stage of the boriding reaction. The bearing steel obtained in this way has better wear resistance, strength and toughness.
[0036] In summary, this application has the following beneficial effects:
[0037] 1. This application takes 20CrNiMo low-carbon bearing steel as the research object. By controlling the amount of carbon, silicon, manganese, chromium, nickel, molybdenum and vanadium in the matrix components, salt bath boronizing is carried out in combination with a boronizing agent composed of Na2B4O7, Al, and KCl, and the thickness of the boronized layer is strictly controlled. The boronized bearing steel thus obtained maintains the high strength and toughness of the matrix while significantly improving the surface hardness, wear resistance and other properties, and can be well used in the bearings of roller drill bits.
[0038] 2. In the boriding process, the present application adds ammonium chloride in combination with other boriding agents, which can further improve the bonding strength between the boriding layer and the substrate, and improve the wear resistance, strength and toughness of the boriding layer.
[0039] 3. The present application adds the boronizing agent in batches and adopts water quenching and boiling water washing and tempering, thereby enabling the matrix to better bond with the carburized layer and have higher toughness and strength.
[0040] 4. The present application avoids the competitive reaction of ammonium chloride with sodium tetraborate and metallic aluminum in the early stage of the boronizing reaction by adding ammonium chloride after the mixed powder is completely melted. The bearing steel obtained thereby has better wear resistance and toughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is an OM diagram of the morphological distribution of the OM matrix structure in Example 1 of the present application; wherein, the left diagram is magnified 500 times, and the right diagram is magnified 200 times.
[0042] Figure 2 It is a morphology distribution diagram of the OM diffusion layer + matrix structure in Example 1 of the present application, specifically two schematic diagrams magnified 200 times at different angles.
[0043] Figure 3 It is a morphology distribution diagram of the OM diffusion layer + matrix structure in Example 1 of the present application, specifically two schematic diagrams magnified 500 times at different angles.
[0044] Figure 4 It is the SEM morphology distribution diagram of the matrix structure in Example 1 of the present application, specifically two schematic diagrams magnified 5000 times at different angles.
[0045] Figure 5 It is the SEM morphology distribution diagram of the matrix structure in Example 1 of the present application, specifically two schematic diagrams magnified 2000 times at different angles.
[0046] Figure 6 It is the SEM morphology distribution diagram of the diffusion layer + matrix structure in Example 1 of the present application, specifically four schematic diagrams magnified 2000 times at different angles.
[0047] Figure 7 It is the SEM morphology distribution diagram of the diffusion layer + matrix structure in Example 1 of the present application, specifically two schematic diagrams magnified 1000 times at different angles.
[0048] Figure 8 This is a diagram of the hardness test results of Example 1 of the present application.
[0049] Fig. 9 This is a diagram showing the friction and wear test results of Example 1 of the present application. DETAILED DESCRIPTION
[0050] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0051] The raw materials of the present application are all from commercially available products. The present application is further described in detail below in conjunction with the accompanying drawings, embodiments and comparative examples.
[0052] Example
[0053] Example 1
[0054] This embodiment discloses a boronized bearing steel, and a preparation method thereof comprises the following steps:
[0055] (1) Preparation of 20CrNiMo steel billet: Based on 1 kg of matrix, accurately weigh 2.0 g of C powder, 3.0 g of Si powder, 8.1 g of Mn powder, 5.1 g of Cr powder, 6.6 g of Ni powder, 4.4 g of Mo powder, and 2.0 g of V powder, and make up the balance with Fe powder. Put the above into a melting furnace for mixing and melting, and then pour into a mold for preparing bearings to form a 20CrNiMo steel billet;
[0056] (2) Heat treatment: 950 g of borax (Na2B4O7·10H2O), 40 g of aluminum powder, and 280 g of potassium chloride powder were preheated and dehydrated, and then crushed to form a mixed powder. The 20CrNiMo steel billet was placed in a salt bath furnace, and one-third of the mixed powder was first added. The temperature was raised to 1000°C at a heating rate of 8°C / min. The remaining mixed powder was added twice during the heating process and stirred evenly. The first time, one-third of the mixed powder was added when the system was heated to 680°C, and the second time, the remaining one-third of the mixed powder was added when the system was heated to 820°C. After the mixed powder was melted and no longer expanded, stirring was stopped, the furnace cover was covered and kept warm for 4 h, and after the insulation was completed, it was directly placed in water and quenched to room temperature to obtain a boronized bearing coarse material;
[0057] (3) Tempering: The boronized bearing rough material is first placed in boiling water for 1 hour, and the residual salt on the surface is removed with a soft brush, and then cleaned with alcohol in an ultrasonic cleaner. After drying, it is stored in a vacuum to obtain the boronized bearing steel. The microstructure of the sample after boronizing and quenching is observed by OM and SEM respectively. The results are shown in Figures 1 to 7 As can be seen from the figure, the matrix structure of the sample after quenching is mainly composed of lath martensite and flake martensite. After measurement, it can be seen that the thickness of the boronized layer is about 30-50μm.
[0058] Embodiment 2-4
[0059] Example 2-4 Based on the method of Example 1, the amount of raw materials used in preparing the 20CrNiMo steel billet is adjusted, and the main components of the corresponding matrix are shown in Table 1 below.
[0060] Table 1 Composition table of the matrix of Examples 1-4 (unit: %)
[0061]
[0062] The thickness of the boronized layer after measurement in Example 2 is about 20-55 μm, the thickness of the boronized layer after measurement in Example 3 is about 60-80 μm, and the thickness of the boronized layer after measurement in Example 4 is 40-65 μm.
[0063] Embodiment 5-7
[0064] In Examples 5-7, based on the method of Example 1, the process parameters of the preparation heat treatment and tempering are adjusted. The corresponding adjustment parameters are shown in Table 2 below.
[0065] Table 2 Process parameters of Example 1 and Examples 5-7
[0066]
[0067] The thickness of the boronized layer after measurement in Example 5 is about 35-60 μm, the thickness of the boronized layer after measurement in Example 6 is about 25-60 μm, and the thickness of the boronized layer after measurement in Example 7 is 25-50 μm.
[0068] Embodiment 8-9
[0069] In Examples 8-9, based on the method of Example 1, the amounts of components of the mixed powder in the heat treatment step were adjusted.
[0070] Among them, in Example 8, 950g of borax (Na2B4O7·10H2O), 30g of metal aluminum powder, and 250g of potassium chloride powder were preheated and dehydrated and then crushed to form a mixed powder. The thickness of the boronized layer of the corresponding boronized bearing steel obtained after measurement was about 20-55μm.
[0071] In Example 9, 950 g of borax (Na2B4O7·10H2O), 50 g of metal aluminum powder, and 300 g of potassium chloride powder were preheated and dehydrated and then crushed to form a mixed powder. The thickness of the boronized layer of the corresponding boronized bearing steel obtained was measured to be approximately 30-65 μm.
[0072] Example 10
[0073] Based on the method of Example 1, this embodiment adjusts the method of adding the mixed powder in the heat treatment step. The difference after the adjustment is that after the 20CrNiMo steel billet is put into the salt bath furnace, the mixed powder is put into the salt bath furnace at one time for salt bath boronizing. The thickness of the boronized layer of the corresponding boronized bearing steel obtained after measurement is about 25-65μm.
[0074] Embodiment 11
[0075] Based on the method of Example 1, this embodiment adjusts the method of adding the mixed powder in the heat treatment step. The difference after the adjustment is that after the 20CrNiMo steel billet is put into the salt bath furnace, half of the mixed powder is added first, and the temperature is raised to 1000°C at a heating rate of 8°C / min. During the heating process, when the temperature reaches 680°C, the remaining half of the mixed powder is added for salt bath boronization. The thickness of the boronized layer of the corresponding boronized bearing steel obtained after measurement is about 30-60μm.
[0076] Examples 12-16
[0077] Examples 12-16 Based on the method of Example 1, the components of the boronizing agent in the heat treatment step are adjusted. The boronizing agent further contains NH4Cl in addition to the original Na2B4O7, Al and KCl. The specific heat treatment steps are as follows:
[0078] 950g of borax (Na2B4O7·10H2O), 40g of metal aluminum powder and 280g of potassium chloride powder are preheated and dehydrated, and then crushed to form a mixed powder. At the same time, 0.2-0.6 times the weight of ammonium chloride powder of Na2B4O7 is preheated and dehydrated, and then a 20CrNiMo steel billet is put into a salt bath furnace, and one third of the mixed powder is added first, and the temperature is increased to 1000°C at a heating rate of 8°C / min. During the heating process, the remaining mixed powder is added twice and evenly stirred. The first time, one third of the mixed powder is added when the system is heated to 680°C, and the second time, the remaining one third of the mixed powder is added when the system is heated to 820°C. After the mixed powder is melted, the preheated and dehydrated ammonium chloride powder is added and ammonia is continuously introduced. After the system no longer expands, the stirring is stopped, the furnace cover is covered and kept warm for 4 hours, and after the insulation is completed, it is directly placed in water and quenched to room temperature to obtain a boronized bearing coarse material.
[0079] Among them, 100g of ammonium chloride powder was added in Example 12, 150g of ammonium chloride powder was added in Example 13, 200g of ammonium chloride powder was added in Example 14, 250g of ammonium chloride powder was added in Example 15, and 300g of ammonium chloride powder was added in Example 16. The thickness of the boronized layer after measurement of the boronized bearing steels obtained in Examples 12-16 was about 40-55μm.
[0080] Embodiment 17
[0081] Example 17 Based on the method of Example 14, the addition method of the boronizing agent in the heat treatment is adjusted. The difference after the adjustment is that after the 20CrNiMo steel billet is put into the salt bath furnace, the mixed powder and the ammonium chloride powder are mixed and put into the salt bath furnace at one time for salt bath boronizing. The thickness of the boronized layer of the corresponding boronized bearing steel obtained after measurement is about 30-65μm.
[0082] Comparative Example
[0083] Comparative Example 1
[0084] In this comparative example, based on the method of Example 1, the amount of raw materials used in preparing the 20CrNiMo steel billet was adjusted, and the main component table of the corresponding matrix is shown in Table 1 above;
[0085] After quenching, the obtained boronized bearing steel sample has a matrix structure mainly composed of lath martensite and a lower density than that of Example 1. The thickness of the boronized layer is measured to be about 15-70 μm.
[0086] Comparative Example 2
[0087] In this comparative example, based on the method of Example 1, the components of the boronizing agent in the heat treatment step are adjusted, specifically, the metal aluminum powder is replaced by aluminum oxide powder, that is, the boronizing agent is composed of Na2B4O7, Al2O3 and KCl;
[0088] After quenching, the obtained boronized bearing steel sample has a matrix structure mainly composed of lath martensite and flaky martensite, but the density of the matrix structure is not as good as that of Example 1. The thickness of the boronized layer is about 25-90 μm.
[0089] Comparative Example 3
[0090] In this comparative example, based on the method of Example 12, the components of the boronizing agent in the heat treatment step are adjusted, specifically, the metal aluminum powder is removed and replaced with an equal amount of potassium chloride powder.
[0091] After quenching, the obtained boronized bearing steel sample has a matrix structure mainly composed of lath martensite and a lower density than that of Example 1. The thickness of the boronized layer is measured to be about 55-95 μm.
[0092] Comparative Example 4
[0093] In this comparative example, based on the method of Example 12, the components of the boronizing agent in the heat treatment step are adjusted, specifically, the potassium chloride powder is removed and replaced with an equal amount of metallic aluminum powder.
[0094] After quenching, the obtained boronized bearing steel sample has a matrix structure mainly composed of lath martensite and a lower density than that of Example 1. The thickness of the boronized layer is about 80-120 μm after measurement.
[0095] Comparative Example 5
[0096] Based on the method of Example 1, this comparative example adjusts the component dosage of the boronizing agent in the heat treatment step. Specifically, 950g of borax (Na2B4O7·10H2O), 140g of metal aluminum powder, and 280g of potassium chloride powder are preheated and dehydrated and then crushed to form a mixed powder.
[0097] Comparative Example 6
[0098] In this comparative example, based on the method of Example 1, the component dosage of the boronizing agent in the heat treatment step is adjusted. Specifically, 950g of borax (Na2B4O7·10H2O), 40g of metal aluminum powder, and 380g of potassium chloride powder are preheated and dehydrated and then crushed to form a mixed powder.
[0099] Performance testing
[0100] The boronized bearing steels obtained in the above-mentioned Examples 1-13 and Comparative Examples 1-3 were used as samples and subjected to the following performance tests.
[0101] 1. Hardness: The microhardness of the boronized layer was measured using a HV-1000 micro-Vickers hardness tester. The test load was 250 gf, the loading time was 10 s, and the dot position was from the corner of the sample, with a horizontal interval of 100 μm and a vertical interval of 10 μm. A total of 10 points were marked for hardness.
[0102] Table 3 shows the test results of the sample in Example 1 at different positions, and the corresponding hardness value change curve is shown in Figure 8 As shown in the figure, the microhardness gradually decreases from the boronized layer to the substrate. The average microhardness of the boronized layer is about 1560HV, the hardness of the transition layer is about 741HV, and the average microhardness of the substrate is only 457HV. The results show that after boronization, the microhardness value is increased by about 3.4 times. The average microhardness of each layer of other embodiments and comparative examples is shown in Table 4 below.
[0103] 2. Wear resistance: The friction and wear test was carried out using an ML-100C abrasive wear tester, with a counterweight of 8g, a disc speed of 60 rpm, a sample feed of 2mm / rev, a stroke of 60mm, an acceleration and deceleration time of 5ms, and a rotation speed of 30 revs, that is, a single friction and wear time of 30s. After 180s, the mass loss was recorded by weighing;
[0104] Fig. 9The weight loss and wear time variation of the sample of Example 1 during the friction and wear test are given. It can be seen from the figure that the weight loss during the wear test after boronization is small, and the weight loss is slightly accelerated until 90s after wear, but the weight loss is still relatively gentle. Compared with the sample after the boronization layer, the weight loss of the base sample from the beginning to the end of the wear test shows a linear decrease trend with the wear time. The results show that the wear performance of the alloy steel is significantly improved after boronization. The mass loss of other embodiments and comparative examples is shown in Table 4 below.
[0105] 3. Mechanical properties: The upper yield strength R of the sample is determined according to the GB228-2010 test standard. eH , tensile strength R m , Total elongation at break A t And the section shrinkage rate Z, the test results are shown in Table 4 below.
[0106] Table 3 Hardness measurement results of Example 1 (HV 0.025 )
[0107] HV 1 2 3 4 5 6 7 8 9 10 hardness 1668.7 1527.1 1483.7 741.6 472.7 417.2 488.7 417.1 496.5 450.7
[0108] Table 4 Test results of Examples 1-13 and Comparative Examples 1-3
[0109]
[0110]
[0111] According to the records of the above embodiments and comparative examples, combined with Table 4, the test results of embodiments 1-17 and comparative examples 1-6 are compared and analyzed to obtain that the matrix structure of the boronized bearing steel of the present application after quenching is mainly composed of lath martensite and lamellar martensite. In terms of the thickness of the boronized layer, the thickness of the boronized layer after the boronization treatment of the present application is controlled to be 20-80μm, and the thickness range is narrower than that of the comparative example. In terms of microhardness, the average microhardness of the boronized layer of the present application is about 1475-1611HV, and the average microhardness of the matrix is about 435-467HV. The microhardness value after boronization is increased by about 3.4 times or more, which is better than the microhardness improvement efficiency of the comparative example. In terms of wear resistance, the mass loss of the present application is lower; in terms of mechanical strength, the yield strength of the present application is 985-1043MPa, and the tensile strength is 1269-1340MPa, which are significantly better than the comparative example; in terms of toughness, the total elongation at break of the present application is 30.7-44.5%, and the cross-sectional shrinkage is 59.2-71.2%, which are also higher than the comparative example.
[0112] Therefore, this application takes 20CrNiMo low-carbon bearing steel as the research object, controls the amount of carbon, silicon, manganese, chromium, nickel, molybdenum and vanadium in the matrix components, and carries out salt bath boronizing in combination with a boronizing agent composed of Na2B4O7, Al, and KCl, and strictly controls the thickness of the boronized layer. The boronized bearing steel obtained in this way significantly improves the surface hardness, wear resistance and other properties while maintaining the high strength and toughness of the matrix, and can be well used in the bearings of roller drill bits.
[0113] Further analyzing the test results of Examples 1-7 and Comparative Example 1, it can be found that a slight adjustment of the amount of raw materials used to prepare 20CrNiMo steel billets and the process parameters of heat treatment and tempering will lead to the performance of boronized bearing steel. Therefore, the amount of raw materials of each component and the process parameters of the present application need to be strictly controlled.
[0114] By analyzing the test results of Example 1, Examples 8-9 and Comparative Examples 2-6, it can be obtained that the main components of the boriding agent in the present application must be composed of Na2B4O7, Al and KCl in a weight ratio of 1:0.06-0.10:0.5-0.6. The borided bearing steel obtained in this way can significantly improve its surface hardness, wear resistance and other properties while maintaining the high strength and toughness of the matrix, and thus can be better applied to the bearings of roller drill bits. It can be seen from the test results of Example 1, Example 12, and Examples 2-6 that by selecting and adding specific proportions of Al, KCl, and ammonium chloride as boriding agent components, the mechanical properties of the borided bearing steel are better than using the same amount of two of them as boriding agent components alone, indicating that the three components combined with borax as a boriding agent achieve a synergistic improvement effect.
[0115] By analyzing the test results of Example 1 and Examples 10-11, it can be obtained that the present application adopts the method of adding the mixed powder corresponding to the boronizing agent in batches to obtain boronized bearing steel with better performance. Further, the method of adding in three times is adopted, and the boronized bearing steel obtained thereby has better microhardness, wear resistance, mechanical strength and toughness.
[0116] By analyzing the test results of Example 1 and Examples 12-16, it can be found that the application adds an appropriate amount of ammonium chloride, which can be used in combination with other boronizing agents (Na2B4O7, Al, KCl), which can further improve the bonding strength between the boronized layer and the substrate, and improve the wear resistance, strength and toughness of the boronized layer. The amount of ammonium chloride added needs to be strictly controlled according to the "weight ratio of Na2B4O7 to NH4Cl is 1:0.3-0.5", so that the role of ammonium chloride can be effectively exerted to ensure the wear resistance, strength and toughness of the boronized layer.
[0117] By analyzing the test results of Example 14 and Example 17, it can be obtained that in the present application, ammonium chloride is added after the boriding agent is completely melted. At this time, the sodium tetraborate, metallic aluminum and potassium chloride in the boriding agent have initially completed the reaction, thereby avoiding the competition reaction of ammonium chloride with sodium tetraborate and metallic aluminum in the early stage of the boriding reaction. The bearing steel obtained in this way has more excellent microhardness, wear resistance, strength and toughness.
[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A boronized bearing steel, characterized in that: The invention comprises a substrate and a boriding layer; the substrate is 20CrNiMo steel, comprising the following components in weight percentage: C 0.18-0.22wt%, Si 0.25-0.32wt%, Mn 0.75-0.83wt%, Cr 0.48-0.55wt%, Ni 0.50-0.70wt%, Mo 0.40-0.50wt%, V 0.18-0.21wt%, and the balance is Fe and inevitable impurities; the boriding layer is obtained by salt bath boriding, the boriding agent of the salt bath boriding is mainly composed of Na2B4O7, Al and KCl, the weight ratio of Na2B4O7, Al and KCl is 1:0.06-0.10:0.5-0.6, and the thickness of the boriding layer is 20-80μm.
2. The boronized bearing steel according to claim 1, characterized in that: The boronizing agent also includes NH4Cl.
3. The boronized bearing steel according to claim 2, characterized in that: The weight ratio of Na2B4O7 to NH4Cl is 1:0.3-0.
5.
4. The method for preparing the boronized bearing steel according to claim 1, characterized in that: The following steps are involved: Preparing a 20CrNiMo steel billet: Preparing a 20CrNiMo steel billet according to the component ratio of the matrix; Heat treatment: the boronizing agent is preheated and dehydrated, and then crushed to form a mixed powder. The 20CrNiMo steel billet is put into a salt bath furnace, a portion of the mixed powder is added first, and the temperature is raised to the austenitizing temperature. During the heating process, the remaining mixed powder is added in batches and stirred evenly. After the mixed powder is melted and no longer expands, the stirring is stopped, and the furnace cover is covered for insulation. After the insulation is completed, it is directly placed in water and quenched to room temperature to obtain a boronized bearing rough material; Tempering: The boronized bearing rough material is first placed in boiling water for boiling and washing, then cleaned with alcohol, and then dried and stored in a vacuum to obtain the boronized bearing steel.
5. The preparation method according to claim 4, characterized in that: In the heat treatment step, the austenitizing temperature is 980-1030° C. and the holding time is 3-5 hours.
6. The preparation method according to claim 4, characterized in that: In the heat treatment step, the temperature is increased at a rate of 5-10°C / min.
7. The preparation method according to claim 4, characterized in that: In the heat treatment step, the remaining mixed powder is added twice, the first time when the system is heated to 650-700°C, and the second time when the system is heated to 800-850°C.
8. The preparation method according to claim 4, characterized in that: In the tempering step, the boiling and washing time is 0.8-1.5h.
9. The method for preparing the boronized bearing steel according to claim 2 or 3, characterized in that: The following steps are involved: Preparing a 20CrNiMo steel billet: Preparing a 20CrNiMo steel billet according to the component ratio of the matrix; Heat treatment: preheat and dehydrate Na2B4O7, Al, and KCl and grind them to form a mixed powder. Simultaneously, preheat and dehydrate NH4Cl and grind them to form NH4Cl powder. Put the 20CrNiMo steel billet into a salt bath furnace, add a portion of the mixed powder first, heat it to the austenitizing temperature, add the remaining mixed powder in batches during the heating process and stir evenly, add NH4Cl powder after the mixed powder is melted and continuously introduce ammonia, stop stirring after the system stops expanding, cover the furnace for insulation, and directly put it in water for quenching to room temperature after the insulation is completed to obtain a boronized bearing coarse material; Tempering: The boronized bearing rough material is first placed in boiling water for boiling and washing, then cleaned with alcohol, and then dried and stored in a vacuum to obtain the boronized bearing steel.
Citation Information
Patent Citations
Surface boronizing treatment method of steel piece
CN102051572A
High-pressure-resisting and low-carbon alloy steel material
CN102634737A
Method for improving wear resistance and self-lubricating property of high-entropy alloy through electrochemical liquid boriding
CN113445098A
Special alloy steel boriding process based on 00Cr and product thereof
CN116752083A
Enhanced efficiency electro-enhancement process for surfaces
US20170088966A1